Exon skipping in CYBB mRNA and skewed inactivation of X chromosome cause late-onset chronic granulomatous disease. (18th August 2018) - Eguchi, Mariko; Yagi, Chihiro; Tauchi, Hisamichi; Kobayashi, Masao; Ishii, Eiichi; Eguchi-Ishimae, Minenori
Abstract: Chronic granulomatous disease (CGD) is a hereditary immunodeficiency syndrome caused by a defect in the NADPH oxidase complex, which is essential for bactericidal function of phagocytes. Approximately 70% of patients with CGD have a mutation in the CYBB gene on the X chromosome, resulting in defective expression of gp91 phox, one of the membrane-bound subunits of NADPH oxidase. Although most patients with X-linked CGD are males, owing to transmission of this disease as an X-linked recessive trait, there are female patients with X-linked CGD. Here, we report the case of a teenage girl with X-linked CGD associated with a heterozygous mutation in exon 5 of the CYBB gene (c.389G > C; R130P), which causes skipping of exon 5, resulting in a premature stop codon in exon 6 of CYBB . Accurate pro-mRNA splicing for mature mRNA formation is regulated by several splicing mechanisms that are essential for appropriate recognition of exonic sequences. The c.389G > C mutation disrupts exonic-splicing regulator sequences, thereby resulting in the aberrant skipping of exon 5 in the CYBB transcript of the patient. The patient showed an extremely skewed (≥96%) X inactivation pattern of the HUMARA locus; this inactivation is thought to be responsible for the development of CGD not only in neutrophils but also in monocytic, T-cell, and B-cell lineages and in CD34-positive immature hematopoietic cells. Our case and other reports indicate that the onset of X-linked CGD in female patients tends to occur later in life, and that the symptoms tend to be milder as compared to male patients.